2020
DOI: 10.1177/1078155220907674
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the delivery of care to oncology patients in the United States: Emphasis on the role pharmacists on the healthcare team

Abstract: Objective The purpose of this study was to identify trends in oncology care that allow one to forecast workforce supply and demand, the training and skills needed by the oncology pharmacist for the likely future of oncology care. Methods Interviews were conducted with experienced oncology pharmacists in leadership roles at 20 organizations balanced by geographic region and type of practice site (academic or community/ambulatory). Results were analyzed using descriptive statistics and theme identification. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Four papers are qualitative (Farrell et al, 2017 ; Hobson et al, 2009 ; Lennan, 2014 ; Siouta et al, 2019 ), two of which use ethnography (Farrell et al, 2017 ; Siouta et al, 2019 ), one grounded theory approach (Hobson et al, 2009 ) and one participatory evaluation (Lennan, 2014 ). Two papers used mixed methods (Farrell et al, 2020 ; Ignoffo et al, 2021 ); eight are observational studies (Bruinooge et al, 2018 ; Dennison et al, 2021 ; Farrell et al, 2010 ; Lam & Cheung, 2016 ; Maier et al, 2018 ; Patel et al, 2016 ; Simons et al, 2010 ; Towle et al, 2011 ); and one used a Delphi design (Ignoffo et al, 2016 ). Two papers (Farrell et al, 2020 ; Siouta et al, 2019 ) undertook secondary analysis on primary data collected in an ethnographic study (Farrell et al, 2017 ) and all three are therefore included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four papers are qualitative (Farrell et al, 2017 ; Hobson et al, 2009 ; Lennan, 2014 ; Siouta et al, 2019 ), two of which use ethnography (Farrell et al, 2017 ; Siouta et al, 2019 ), one grounded theory approach (Hobson et al, 2009 ) and one participatory evaluation (Lennan, 2014 ). Two papers used mixed methods (Farrell et al, 2020 ; Ignoffo et al, 2021 ); eight are observational studies (Bruinooge et al, 2018 ; Dennison et al, 2021 ; Farrell et al, 2010 ; Lam & Cheung, 2016 ; Maier et al, 2018 ; Patel et al, 2016 ; Simons et al, 2010 ; Towle et al, 2011 ); and one used a Delphi design (Ignoffo et al, 2016 ). Two papers (Farrell et al, 2020 ; Siouta et al, 2019 ) undertook secondary analysis on primary data collected in an ethnographic study (Farrell et al, 2017 ) and all three are therefore included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven papers are hospital based (Dennison et al, 2021 ; Farrell et al, 2010 ; Farrell et al, 2017; Farrell et al, 2020 ; Ignoffo et al, 2016 ; Lam & Cheung, 2016 ; Lennan, 2014 ; Maier et al, 2018 ; Patel et al, 2016 ; Simons et al, 2010 ; Siouta et al, 2019 ) and four are hospital and community based (Bruinooge et al, 2018 ; Hobson et al, 2009 ; Ignoffo et al, 2021 ; Towle et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, Maryam et al in their cross-sectional study have reported the mean scores of responses for knowledge, attitude, and practice which were observed to be 54.30 ± 10.86, 32.83 ± 5.88, and 50.35 ± 10.21, respectively. 18 In current study, the increase in the mean score of these parameters depicts the positive effect of training the HCPs using standard guidelines while handling, preparation and administration of anti-cancer drugs by clinical oncopharmacist Similarly, Ali et.al have demonstrated in their study that involvement of clinical oncology pharmacist plays an integral role in minimizing the adverse effect and in raising safety standards 19 while handling the CDs and also, Robert et al have highlighted the importance of the training the oncology pharmacist for the better future of oncology care 20…”
Section: Discussionmentioning
confidence: 96%
“…1 Oncology pharmacists are integral in the safe care of patients and remain a sustained need supported by trends in cancer incidence and mortality. 2 Despite the role for these pharmacists being well defined and the expanding responsibilities previously described, position justification for pharmacists is a challenge with prerequisites to optimize efficient processes, promote quality and reduce overall costs. 3,4 Initiation and implementation of new oncology pharmacist services requires a clear description of value to the organization and a strong understanding of workflows.…”
Section: Introductionmentioning
confidence: 99%